THE COGNITIVE FUNCTION OF ANTHRACYCLINE-BASED ADJUVANT CHEMOTHERAPY IN WOMEN WITH BREAST CARCINOMA - Sukendro Sendjaja; Ibnu Purwanto; Johan Kurnianda (Acta Interna The Journal of Internal Medicine, 2011)
ABSTRACT Objective. The objective of this study was to determine the changes cognitive function of anthracycline-based adjuvant chemotherapy in women with breast carcinoma.Method. The study design was prospective longitudinal study. The breast cancer patients who received anthracycline-based adjuvant chemotherapy were recruited from internal medicine wards and TULIP outpatient department Dr. Sardjito General Hospital Yogyakarta. Subjects eligible with inclusion and exclusion criteria were examined for cognitive function by mini-mental state examination (MMSE) before chemotherapy (T0), 3 weeks after 2nd adjuvant chemotherapy (T1), 3 weeks after 4th adjuvant chemotherapy (T2), and 3 months after 4th adjuvant chemotherapy (T3). The mean difference of MMSE scores were analyzed with Wilcoxon-signed rank test and P<0.05 was considered statistically significant.Result. There were 47 subjects eligible to study criteria in October 1st 2008 – October 31st 2009. Forty subjects finished this study and were analyzed. The mean age was 47.08±6.65 with age ranged from 27 to 61 years old. The mean MMSE scores before chemotherapy (T0), 3 weeks after 2nd adjuvant chemotherapy (T1), 3 weeks after 4th adjuvant chemotherapy (T2), and 3 months after 4th adjuvant chemotherapy (T3) were 29.28±1.20, 28.60±1.69, 28.18±1.89, and 27.85±2.03, respectively. The mean MMSE score changes (ΔT0-T1), (ΔT0-T2), and (ΔT0-T3) were 0.68±0.80, 1.10±1.06, and 1.43±1.36, respectively and P<0,001. The incidence of cognitive impairment with MMSE scores < 24 was 2.5% and P=1.0.Conclusion. There was a significant decline of MMSE score in women with breast carcinoma who received anthracycline-based adjuvant chemotherapy at 3 weeks after 2nd adjuvant chemotherapy, 3 weeks after 4th adjuvant chemotherapy, and 3 months after 4th adjuvant chemotherapy compared with before chemotherapy. Key Words: Cognitive Function, Breast Cancer, Adjuvant Chemotherapy, Anthracycline